Permanências na mudança, identidades em questão : significados da docência entre formadores de professores de Educação em Ciências em um modelo educacional em construção - Cavalcanti, Alberes de Siqueira (2016)
With the creation of the Federal Institutes of Education, Science and Technology and the Magisterium role of Basic Education, Technical and Technological (EBTT), a new scenario emerges for the education of teachers in Brazil. The Federal Institutes begin to offer teacher education courses for basic education, especially in science and mathematics. The EBTT teacher begins by working in basic education and higher education. This is the context of changes and institutional reconfigurations and teaching staff which is the research presented here. Its objectives were to identify the educational profile of science teacher trainers; discuss the vision of education and science in the teaching identity configuration; analyze and interpret the discursive construction of teacher identity of teacher educators. It is a qualitative research in the narrative modality that had as its locus the Federal Institute of Maranhão Campus São Luís Monte Castle, with the participation of teacher trainers of undergraduate courses in Physics, Chemistry and Biology. The corpus of research was built by interviews, meetings with the participants, pedagogical projects of the courses. For the analytical procedure, we adopted the discursive textual analysis. We defend the thesis that the socio-institutional processes of change in new meanings are (self)assigned to teaching, which sometimes tend in their conceptions and practices for the conservation and the traditional, now tend to the change and the new, implying that what sets the trend for a hub or another is not so much what is established by institutional models, but by the feeling of belonging and confirmation or validation of a teaching body; thus, a meaning if consolidates or not in the configuration of the teacher identity in accordance with the degree of sharing of practices and discourses in a given educational institution. The thesis is woven in scenarios that are interwoven, intended to demonstrate the various places, contexts, speeches and actors involved in the narrative. The narrative leads to consider that: - the teacher identity is built in a dynamic and continuous process of identification and differentiation, construction and reconstruction of the practices, of the values, the relations established with the other and the work environment; - the changes are not imposed as faithful copies of speeches regulators, there are always adaptations and mutations put into motion by teachers that in teaching practice executing the acceleration rate or delaying it, legitimation or denial of changes; - the change implemented in the magisterium role is the cause of "teaching"; from the actions of the EBTT Professor, there is the possibility of approximation between the levels of education in their own process of teacher training; - coexist two discursive lines (pragmatic and critical) that make converge The visions of education, science and research in training and teachers; - identity emerge "" silences concerning education in science, which may denote the permanence of the vestiges of a trend bachelorhood education; - there is a disparity between the speed with which the statutory changes are performed and the slowness with which the working conditions are guaranteed, remaining internal obstacles relating to infrastructure and to the collective work.